DIAGNOSTIC EXAMINATION AND APPROACHES IN ADOLESCENTS WITH A HIGH RISK OF ALCOHOLISM - Dilnoza Hamidullayevna, Xushvaktova (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: The aim of this study is to explore the efforts of public health professionals, including scientists, narcologist-practitioners, and teachers, in addressing the issues of alcoholism and drug addiction. This includes promoting medical and legal knowledge, as well as providing preventive and therapeutic measures. Methods: The study investigates the methods employed in the prevention of alcoholism and drug addiction, including public lectures, visual propaganda (posters, booklets, etc.), and media campaigns. It also explores the role of a specialized drug service that offers medical-preventive, medical-social, and medico-legal support to individuals affected by addiction. Results: The findings reveal that these methods contribute to raising awareness about addiction and its consequences. The media, both traditional and digital, plays a significant role in reaching a broader audience, while the drug service provides essential assistance in managing and treating addiction cases. Novelty: This study highlights the integrated approach involving education, public campaigns, and specialized medical services in addressing the complex issue of addiction. It emphasizes the importance of both preventive and therapeutic interventions in tackling alcoholism and drug dependency.